Masalah-masalah Pada Remaja dan Implikasinya Pada Pendidikan - Rahayu, Arum Dewi; Nursyafitri, Dila; Sitepu, Fatimah Azzahra; Hairani, Mutiara; Harahap, Salsabilah; Nasution, Salsabila; Lubis, Ramadan (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research generally aims to find out how problems occur during adolescence. The specific aim of this research is to find out the problems that occur during adolescence, to find out the factors that cause problems during adolescence, to find out the efforts of parents and teachers in helping solve adolescent problems, and the implications for education. The sample for this research was 2 teenagers, the type of research used was field research, namely research carried out directly in the field. The data collection methods used were interviews, observation and documentation. The results of this research are that communication between parents and teenagers is going quite well. The causes of adolescent problems include limited time between parents and children, monotonous messages from parents and teachers, one-way communication, parents and teachers not understanding the characteristics of children, the desire to argue rather than understand teenagers, and obstacles from the home environment. as well as school. The conclusion of this research is that teenagers are easily influenced by their friends, but parents and teachers can also prevent teenagers from teenage problems by providing love, advising, guiding, supervising and providing motivation.